The management of student success in extended curriculum programmes: A case study of the University of Pretoria’s Mamelodi Campus, South Africa - Ogude, N. A.; Majozi, P. C.; Mathabathe, K. C.; Mthethwa, N. (South African Journal of Higher Education, 2021)
For three decades, numerous South African scholars have researched the efficacy of access programmes in providing alternative pathways to careers in Science, Technology, Engineering and Mathematics through foundation provisioning. In light of this, Extended Curriculum Programmes (ECPs) were designed for talented Black students who could not gain access to tertiary studies due to poor schooling conditions caused by apartheid. As scarce skills programmes that receive dedicated funding from government, ECPs are indispensable for redress, transformation, and socio-economic development. Consequently, they could be characterized as high stakes programmes that require a rigorous, evidence-led student success management approach to ensure effectiveness. This article argues for a customized approach to the management of student success for ECPs based on the Institutional Student Academic Development and Excellence Model. Using specific examples, the customized system, dubbed the Mamelodi Referral System, is discussed as well as the circumstances that led to its development. The article concludes with future areas for development and refinement.